Reaching the Unreachable: Novel Approaches to Telemedicine Screening of Underserved Populations for Vitreoretinal Disease. (3rd July 2017) - Murchison, Ann P.; Haller, Julia A.; Mayro, Eileen; Hark, Lisa; Gower, Emily; Huisingh, Carrie; Rhodes, Lindsay; Friedman, David S.; Lee, David J.; Lam, Byron L.; ,
ABSTRACT: Telemedicine involves electronic communication between a physician in one location and a patient in another location to provide remote medical care. Ophthalmologists are increasingly employing telemedicine, particularly in retinal disease screening and monitoring. Telemedicine has been utilized to decrease barriers to care and yield greater patient satisfaction and lower costs, while maintaining high sensitivity and specificity. This review discusses common patient barriers to eye care, innovative approaches to retinal disease screening and monitoring using telemedicine, and eye care policy initiatives needed to enact large-scale telemedicine eye disease screening programs.